ANALISIS FAKTOR YANG MEMPENGARUHI TERJADINYA BURNOUT SYNDROME PERAWAT DI RUANG CRITICAL CARE - Handayani, Fitriya; Ose, Maria Imaculata; Hidaya, Nurman; Hasriana (JURNAL KESEHATAN INDRA HUSADA, 2024)
Burnout syndrome is a collection of physical, psychological and mental symptoms that are destructive due to monotonous and stressful work fatigue. The part of nurses who are prone to burnout syndrome is nurses who handle emergency patients. Nurses who handle emergency patients include ICU (Intensive care unit), HCU (high care unit), and IGD (emergency room), due to higher job demands than nurses in other inpatient rooms. This study aims to get an idea of the incidence of burnout syndrome in nurses in the Critical Care Room and see the factors that influence it. This type of research is quantitative research with descriptive design. This study involved 38 respondents who were nurses who served in the critical care room. The results showed that the majority of respondents experienced low category burnout as many as 18 people (47.4%). Statistical test results showed a meaningful relationship between individual factors and organizational factors with nurse burnout syndrome. The most dominant factor to the occurrence of burnout syndrome can be seen from the results of multivariate analysis that the value of OR the largest and significant value is the organizational factor with a value of OR 5.907. This shows that organizational factors are the most influential factors 5,907 times to the occurrence of burnout syndrome nurse than other factors. Keywords: burnout syndrome, nurses, critical care